2015
DOI: 10.1016/j.freeradbiomed.2015.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress response and Nrf2 signaling in aging

Abstract: Increasing oxidative stress, a major characteristic of aging, has been implicated in variety of age-related pathologies. In aging, oxidant production from several sources is increased while antioxidant enzymes, the primary lines of defense, are decreased. Repair systems, including the proteasomal degradation of damaged proteins also declines. Importantly, the adaptive response to oxidative stress declines with aging. Nrf2/EpRE signaling regulates the basal and inducible expression of many antioxidant enzymes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
535
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 691 publications
(556 citation statements)
references
References 405 publications
(447 reference statements)
14
535
3
4
Order By: Relevance
“…By analyzing the nuclear proteins, we showed that OI-stabilized Nrf2 translocated to cell nuclei (Fig. 1C), which is a key step for Nrf2 activation [10,33]. Indeed, we showed that mRNA (Fig.…”
Section: Oi Activated Nrf2 Signaling In Thp-1 Cells and Sle Patient-dmentioning
confidence: 89%
“…By analyzing the nuclear proteins, we showed that OI-stabilized Nrf2 translocated to cell nuclei (Fig. 1C), which is a key step for Nrf2 activation [10,33]. Indeed, we showed that mRNA (Fig.…”
Section: Oi Activated Nrf2 Signaling In Thp-1 Cells and Sle Patient-dmentioning
confidence: 89%
“…miRs could contribute to the modulation of the stress response mediated by Nrf2 at various levels in different physiopathological contexts including neurological disorders [9,40,107]. Firstly, several miRs are directly implicated in Nrf2 post-transcriptional regulation by targeting its mRNA, thus reducing Nrf2 protein levels and, consequentially, stress defenses (Table 1).…”
Section: Oxidative Stress and Micrornasmentioning
confidence: 99%
“…Several works indicate that an optimal activity of Nrf2 is essential to protect cells against different stressors, and that its dysfunction is correlated with decreased tolerance to oxidative/chemical insults [8]. Therefore, alterations of the Nrf2 activity has been linked to the natural aging process [9,10] and to the pathogenesis of many human chronic diseases, including neurodegenerative [reviewed in [11][12][13] and cardiovascular diseases [14], fibrosis [15], inflammatory states [16], as well as with abnormalities in the susceptibility of tumor cells to chemo-and radio-therapy [reviewed in 17,18]. For these reasons, pharmacological/natural strategies that potentiate Nrf2 activity could be beneficial for preventing diseases in which oxidative stress exerts a pivotal role [7,[19][20][21].…”
mentioning
confidence: 99%
“…While observations of redox signaling at the ER are relatively scarce at this stage, it is clear that H 2 O 2 is widely utilized as a signaling molecule in vivo [28] and it is quite predictable that further mechanisms specific to the ER will be uncovered in the future [18]. Other examples, which are connected to H 2 O 2 transit across the ER membrane, are granulocyte colonystimulating factor receptor signaling [29], oxidative DNA damage in response to cellular stresses [30][31][32], activation of survival pathways upon H 2 O 2 generation in the ER [33,34], and the regulatory roles of ER-luminal peroxidases in various settings of cytosolic signal transduction [29,[35][36][37][38].…”
Section: H 2 O 2 Can Readily Permeate Through the Endoplasmic Reticulmentioning
confidence: 99%